Design and Build Automatic Catfish Feeding System Biofloc - Muhammad Naufal Apsara Firyadha Naufal; Nurul Hidayati; Waluyo Waluyo (Jurnal Jaringan Telekomunikasi, 2023)
Catfish is one of the results of freshwater cultivation that is popular with the community and has economic value. The high public interest in catfish, is one of the factors cultivators increase production yields. Feeding and treatment of catfish pond water still uses human resources. This reduces the efficiency of the farmer and allows for negligence in providing feed and water treatment if the farmer has a large number of ponds or more than one. In this study, it is proposed to control and monitor feeding and water treatment with a biofloc system automatically and regularly, with the catfish biofloc system also obtaining natural food when the feeding schedule is raining. It takes a wireless sensor network system as a control system, fc-37 sensor, Total Dissolved Solids (TDS), Loadcell, Real Time Clock (RTC). All of these sensors will be integrated with the Arduino Uno which will then send data from each sensor to the Raspberry Pi with the nRF24l01 communication module. The results of this study are monitoring the appearance of the web server processed by the Raspberry Pi which shows feed availability, pond conditions and turbidity levels. From the experimental results, it is found that the planned system can work well and as desired.